Emendation of the subfamilies Caiguiriinae and Pygidiopsinae (Digenea) with a redescription of Caiguiria anterouteria (Digenea: Heterophyidae) and reassignment of Pygydiopsis crassus to Caiguiria - Dronen, Norman O.; Blend, Charles K.; Davis, Alisha J. (Zootaxa, 2004)
During a study of members of the genus Pygidiopsis from wading birds from the Texas gulf coast, specimens of Caiguiria anterouteria from the United States National Parasite Collection and from the Senckenberg Museum, Frankfurt and specimens of Pygidiopsis macrostomum from the Natural History Museum, London were examined. These specimens demonstrated ranges of characteristics that called in to question their assignment to either Pygidiopsis or Caiguiria. Species of Pygidiopsis are divided into 4 distinct morphological groups based on the presence or absence of spines on the oral sucker, the distribution of the vitellaria and the anterior extent of the uterus. The subfamily Caiguiriinae is emended to include those species with an unarmed oral sucker and vitelline follicles that reach the level of the acetabulum anteriorly, and C. anterouteria is redescribed based on existing museum specimens consistent with the holotype specimen. The genus Caiguiria is emended to include species where the vitelline follicles reach the level of the acetabulum anteriorly but do not extensively invade the postesticular space. Pygidiopsis crassus is assigned to Caiguiria as Caiguiria crassa n. comb., and the subfamily Pygidiopsinae is emended to include those species where the vitelline follicles extend from the level of the acetabulum posteriorly in to the posttesticular space and where the uterus is confined to the hindbody. The validity of Pygidiopsis pelecani and Pygidiopsis piclaumoreli is discussed.